Cloudacc: a cloud-based accountability framework for federated cloud - RODRIGUES, Thiago Gomes (2016)
The evolution of software service delivery has changed the way accountability is performed. The complexity related to cloud computing environments increases the difficulty in properly performing accountability, since the evidences are spread through the whole infrastructure, from different servers, in physical, virtualization and application layers. This complexity increases when the cloud federation is considered because besides the inherent complexity of the virtualized environment, the federation members may not implement the same security procedures and policies. The main objective of this thesis is to propose an accountability framework named CloudAcc, that supports audit, management, planning and billing process in federated cloud environments, increasing trust and transparency. Furthermore, CloudAcc considers the legal safeguard requirements presented in Brazilian Marco Civil da Internet. We confirm the CloudAcc effectiveness when some infrastructure elements were submitted against Denial of Service (DoS) and Brute Force attacks, and our framework was able to detect them. Facing the results obtained, we can conclude that CloudAcc contributes to the state-of-the-art once it provides the holistic vision of the cloud federated environment through the evidence collection considering the three layers, supporting audit, management, planning and billing process in federated cloud environments.